Women's experiences with giving birth before arrival. (November 2016) - Vik, Eline Skirnisdottir; Haukeland, Gunn Terese; Dahl, Bente
Abstract: Objective: To explore women's experiences with giving birth before arrival. Design: A qualitative interview study. Setting: Individual semi structured interviews with women from Western Norway conducted in their homes in 2015. Participants: 10 women who experienced BBA-births in 2014, or the beginning of 2015. Two primiparous and eight multiparous women participated in the study. Key findings: Three themes were generated from the analysis. In the encounter with the healthcare services, the women described midwives as gatekeepers defining active labour. Giving birth before arrival was dramatic, but at some point fear of giving birth alone was replaced by feelings of coping, and in hindsight they felt empowered. The women described giving birth before arrival to be a special experience, but this was not always acknowledged by the midwives. Conclusion and implications for practice: The findings in this study question the cost-benefit of today's maternity care system pointing towards a more differentiated and decentralised care. To enhance patient safety adequate capacity of midwives in the maternity care is essential. Furthermore, good communication skills are key to improving practice and enhancing safety. Further research must be conducted. Highlights: It was hard to define active labour, and this complicated the process. The women felt empowered after taking responsibility in the situation. Communication skills are identified as a key factor to improve today's practice. Midwives are seen as gatekeepers of the labour ward.